The use of flash cards in improving early reading skills in students with mild dyslexia: a single subject study (SSR) - Frida Adha Yusnianingsih; Fendy Yogha Pratama (Jurnal Konseling dan Pendidikan, 2026)
This study aimed to examine the use of flashcards to improve reading skills in third-grade students with mild dyslexia, particularly for words containing diphthongs and consonant clusters. The study used a Single Subject Research (SSR) approach with an A–B–A design over 20 sessions (A1 = 5 sessions, B = 11 sessions, A2 = 4 sessions). Data were collected through reading observation and analyzed using visual charts. The results showed an increase in reading skills from the initial baseline phase (10%–20%) to the intervention phase (up to 80%), with high stability in the final phase (90%–100%). The 18% overlap between phases A1 and B (PND ±82%) indicates a moderately strong intervention effect, although caution should be interpreted, considering data trends and stability. The final baseline phase (A2) consisted of four sessions because the data had consistently shown high stability. Therefore, observations were discontinued after a stable pattern was achieved. These findings suggest that flashcards have the potential to help improve reading fluency. However, because the research only involved one subject (N=1), the research results are limited and cannot be generalized widely, but only apply to similar subject characteristics.